2024
DOI: 10.1186/s12967-024-04989-z
|View full text |Cite
|
Sign up to set email alerts
|

High somatic mutations in circulating tumor DNA predict response of metastatic pancreatic ductal adenocarcinoma to first-line nab-paclitaxel plus S-1: prospective study

Lei Huang,
Yao Lv,
Shasha Guan
et al.

Abstract: Aims We previously showed that the nab-paclitaxel plus S-1 (NPS) regimen had promising effects against metastatic pancreatic ducal adenocarcinoma (mPDAC), whose efficacy however could not be precisely predicted by routine biomarkers. This prospective study aimed to investigate the values of mutations in circulating tumor DNA (ctDNA) and their dynamic changes in predicting response of mPDAC to NPS chemotherapy. Methods Paired tumor tissue and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…2 Genetic analyses have revealed that KRAS mutation importantly drives the pathogenesis of PDAC, prompting an increasing number of investigations into the potential of targeted therapies addressing this genetic alteration. 3,4 Recent advances in molecular targeted therapies, in particular Cyclin Dependent Kinase inhibitors, have shown promise in preclinical studies. 5,6 The recent study by Huang et al 7 presented a compelling application for the targeted agent THZ1, a smallmolecule covalent CDK7/12/13 inhibitor, and provided intriguing insights into its efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Genetic analyses have revealed that KRAS mutation importantly drives the pathogenesis of PDAC, prompting an increasing number of investigations into the potential of targeted therapies addressing this genetic alteration. 3,4 Recent advances in molecular targeted therapies, in particular Cyclin Dependent Kinase inhibitors, have shown promise in preclinical studies. 5,6 The recent study by Huang et al 7 presented a compelling application for the targeted agent THZ1, a smallmolecule covalent CDK7/12/13 inhibitor, and provided intriguing insights into its efficacy.…”
mentioning
confidence: 99%
“…It is also critical to investigate the long-term safety and efficacy of THZ1 and its impact on patient quality of life. The development of liquid biopsy biomarkers that predict response to THZ1 with high specificity is necessary for pancreatic cancer, 3 which can help with the development of personalized therapeutic regi-mens. The understanding of the mechanism of action of THZ1 should also be further enhanced through molecularlevel experiments, to identify the key genes and proteins that are altered following THZ1 treatment.…”
mentioning
confidence: 99%